Role of Renin-Angiotensin System Components in Atherosclerosis: Focus on Ang-II, ACE2, and Ang-1–7 - Silva, Gabriela M.; França-Falcão, Maria S.; Calzerra, Natália Tabosa M.; Luz, Mickael S.; Gadelha, Danilo Duarte A.; Balarini, Camille M.; Queiroz, Thyago M. (Frontiers in Physiology, 2020)
Atherosclerosis is the leading cause of vascular disease worldwide and contributes significantly to deaths from cardiovascular complications. There is a remarkably close relationship between atherosclerotic plaque formation and the activation of renin-angiotensin system (RAS). However, depending on which RAS pathway is activated, pro- or anti-atherogenic outcomes may be observed. This brief review focuses on the role of three of the most important pieces of RAS axis, angiotensin II, angiotensin converting enzyme type 2 and angiotensin 1-7 and their involvement in atherosclerosis. We focused on the effects of these molecules on vascular function and inflammation, which are important determinants of atherogenesis. Furthermore, we highlighted potential pharmacological approaches to treat this disorder.